Hypocholesterolemic Activity of Kedawung (Parkia roxburghii) - Nurul Isnaini Fitriyana; Kosuke Nishi; Takuya Sugahara (Indonesian Journal of Science and Technology, 2021)
The purpose of this study is to investigate the hypocholesterolemic activity of kedawung (Parkia roxburghii), an underutilized and lesss-known tree nut. Kedawung was prepared into kedawung powder (BK), kedawung extract (SK) and hydrolyzed kedawung (HK) and then analyzed for its proximate and total phenol content. Furthermore, SK and HK were administered to rats to evaluate their effects on the lipid profile. Oral administration of HK at 160 mg/kg body weight increased the HDL cholesterol level and lowered the LDL and total cholesterol levels in blood of the administered rats. Among groups of the administered rats that completed the 35-day treatment, total cholesterol and LDL cholesterol were significantly reduced (p0.01). The present data showed that kedawung has a hypocholesterolemic activity because of its phenolic content that acts as antioxidant that can bind cholesterol in blood; composition and distribution of amino acid in HK that changed the cholesterol metabolism (reduced cholesterol concentration); protein content in HK that increased the production of lipoprotein that plays a role in suppression of plaque and atherosclerosis. Therefore, hydrolyzed kedawung can be used as an hypocholesterolemic food material.